1993
DOI: 10.1177/0022427893030001003
|View full text |Cite
|
Sign up to set email alerts
|

Drinking and Driving, Self-Control, and Gender: Testing a General Theory of Crime

Abstract: Recently, Gottfredson and Hirschi proposed a general theory of crime. Central to the theory is the assumption that most criminal behavior is impulsive and reflects a lack of self-control. Thus criminals are seen as risk takers who are less restrained than noncriminals from illegal activities. In a secondary analysis of data from a roadside traffic survey, this study attempts to test Gottfredson and Hirschi's theory by examining the relationship between self-control and driving under the influence of alcohol. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(182 citation statements)
references
References 24 publications
7
171
0
1
Order By: Relevance
“…Since it expects criminality to play itself out in a multitude of ways, including analogous behavior not prohibited by criminal law, it expresses a preference for "behavioral" over "attitudinal" measures (Hirschi and Gottfredson 1993). A classic example is a study explaining driving under influence with the fact that drivers do not use a seatbelt (Keane, Maxim et al 1993). The predecessor study to this meta-study did however not find a significant difference between the use of behavioral and attitudinal measures of low self-control, and it did also not find a significant difference between using the popular attitudinal scale developed by and alternative scales (Pratt and Cullen 2000: 947).…”
Section: D) Empirical Methodologymentioning
confidence: 99%
“…Since it expects criminality to play itself out in a multitude of ways, including analogous behavior not prohibited by criminal law, it expresses a preference for "behavioral" over "attitudinal" measures (Hirschi and Gottfredson 1993). A classic example is a study explaining driving under influence with the fact that drivers do not use a seatbelt (Keane, Maxim et al 1993). The predecessor study to this meta-study did however not find a significant difference between the use of behavioral and attitudinal measures of low self-control, and it did also not find a significant difference between using the popular attitudinal scale developed by and alternative scales (Pratt and Cullen 2000: 947).…”
Section: D) Empirical Methodologymentioning
confidence: 99%
“…One such by Junger et al (1995) found interrelationships between traffic accident involvement, delinquency measures and social control measures, and that Dutch females aged 12-24 had fewer accidents, lower delinquency involvement and more social controls than similarly aged males; another attempt by Keane, Maxim and Teevan (1993) applied elements of self-control, as in Gottfreson and Hirschi's (1990) general theory of crime, to understand drink-driving behaviour among a Canadian roadside sample.…”
Section: Control Explanationsmentioning
confidence: 99%
“…JRCD has published numerous influential articles related to measurement and theoretical development-sometimes looking at the two in tandem (e.g., Farnworth et al 1994). From Gold's (1966) and Hardt and Peterson-Hardt's (1977) articles on measurement of self-reported delinquency within the journal's first 15 years, which still resonate in more recent work assessing the validity of self-reports (e.g., Kim, Fenrich, and Wislar 2000;Paschall, Ornstein, and Flewelling 2001;Wells and Rankin 1995), to Bernard's (1990) overview of theoretical progress (or lack thereof) in criminology, works on measuring self-control within the general theory of crime (see Grasmick et al 1993;Hirschi and Gottfredson 1993;Keane, Maxim, and Teevan 1993), Maltz's (1994) questions about how our methods do and do not serve our substantive goals, Morris and Slocum's (2010) work studying the life events calendar and Boman and colleagues' (2012) consideration of how peer delinquency is measured, this journal has clearly paid attention to important issues in measurement (see also Armstrong, Lee, and Armstrong 2009;Evans and Scott 1984). In the process, authors have both implicitly and explicitly weighed the implications of key measurement issues for knowledge development in the context of individual studies and areas of research more broadly.…”
Section: Lessons For Future Researchmentioning
confidence: 99%
“…While these connections are sometimes clear, overreliance on existing data can lead to imprecision in measurement; 2 indeed, it is only fair to question the consequence of building empirical knowledge of theory from data not specifically intended to test its key tenets. In attempting to leverage available data and measures to test questions of interest, how often are we deviating from, or at least making compromises about, a theory's original propositions (see, e.g., Hirschi and Gottfredson's, 1993, comment on Grasmick et al 1993and Keane, Maxim, and Teevan 1993 3 For instance, many of the studies using measures from NLSY mentioned previously were only able to partially capture key tenets of the focal theory under study. This can complicate our ability to reach definitive conclusions about the empirical support for a theory in single tests as well as entire areas of literature.…”
Section: Measurement Validity In Criminologymentioning
confidence: 99%